Cost-based fire risk assessment in natural gas industry by means of fuzzy FTA and ETA. (January 2020) - Hosseini, Navid; Givehchi, Saeed; Maknoon, Reza
Abstract: Fire is the most prevalent accident in natural gas facilities. In order to assess the risk of fire in a gas processing plant, a fault tree analysis (FTA) and event tree analysis (ETA) has been developed in this paper. By utilizing FTA and ETA, the paths leading to an outcome event would be visually demonstrated. The framework was applied to a case study of processing plant in South Pars gas complex. All major underlying causes of fire accident in a gas processing facility determined through a process hazard analysis (PHA). Fuzzy logic has been employed to derive likelihood of basic events in FTA from uncertain opinion of experts. The outcome events in event tree has been simulated by computer model to evaluate their severity. In the proposed methodology the calculated risk has the unit of cost per year which allows the decision makers to discern the benefit of their investment in safety measures and risk mitigation. Highlights: We have used fuzzy logic to model the uncertainty originating from expert opinion where there is data scarcity. Fuzzy Boolean operations substituted for fuzzy if-then-rules to calculate probability in FTA and ETA. Computer simulation is employed for more accurate consequence analysis of probable outcome events. The calculated risk is expressed in the unit of cost so that it is more concrete.